Visualization of Latent Fingerprints on Papers Using a Ultra-violet Pulsed Laser - AKIBA, Norimitsu; SAITOH, Naoki (Journal of the Visualization Society of Japan, 2006)
We have studied inherent fluorescence spectra of fingerprints and various papers in the deep UV region with a nanosecond pulsed laser system and have visualized latent fingerprints on papers with the time-resolved fluorescence imaging method. The excitation wavelength is 230 nm and 280 nm. Fingerprints emit fluorescence from 300 nm to 500 nm. Since papers also emit fluorescence above 400 nm and it is quite strong, it is necessary to suppress paper fluorescence using filters for imaging latent fingerprints. For printed papers, inks or toners often emit fluorescence. By using appropriate filters, latent fingerprints on papers were visualized for all white and printed papers examined. We have also studied absorption images of fingerprints and obtained clearest images with 215-nm illumination for latent fingerprints on white papers.